Sweden's School Choice Reform and Equality of Opportunity - Karin Edmark; Markus Frölich; Verena Wondratschek (Center for Economic Studies and ifo Institute (CESifo), 2014)
This study analyses whether the Swedish school choice reform, enacted in 1992, had different effects on students from different socio-economic backgrounds. We use detailed geographical data on students' and schools' locations to construct measures of the degree of potential choice. This allows us to study the effects of choice opportunities among public schools, whereas previous studies have focused on newly opened private schools. Our results suggest small positive or no effects of choice opportunities, depending on specification and outcome. We find no strong evidence of differences between subgroups; if anything, effects tend to be slightly more positive for disadvantaged groups, such as students from low-income families. Taken together, the results indicate that students from a socio-economically disadvantaged or immigrant background were not harmed by the reform.
Keywords: I24; C21; 330; school choice; school competition; treatment evaluation; cognitive and non-cognitive skills